Growth of the law - Cardozo, Benjam (New Delhi, 2012)
These lectures, given at the Law School of Yale University in December, 1923 are to be regarded as a supplement to lectures given at the same University in 1921, and published by the Yale University Press under the title of "The Nature of the Judicial Process." Some thoughts imperfectly developed in the first series, seemed to call for fuller and more explicit statement in the second, even at some risk of repetition.
Keywords: Law-Philosophy